Peningkatan Kemampuan Membaca Kritis Siswa MI Najmul Huda melalui Gerakan One Day One Page - I Idammatussilmi (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2020)
The puspose of this research is to develop the School Literary Movement pogram by creating a One Day One Page program to improve students’ critical reading skills. This research is a descriptive study using a qualitative approach. Data analysis is inductive based on facts faound in the field. The result of the fact found in the field are than constructed into hypotheses. Data collegtion techniques using observation, decomentation, ability testing and evaluation. Analysis of students’ needs for understanding critical reading, researchers consider four criteria, namely: (1) the ability to remember and recognize the contents of reading, (2) the ability of studens’ to interpret reading, (3) the ability to apply reading concepts, (4) the ability to analyse reading.